catena-Poly[[(2,2′-bipyridine-κ(2) N,N′)copper(I)]-μ-cyanido-κ(2) C:N-[(2,2′-bipyridine-κ(2) N,N′)copper(I)]-μ-thiocyanato-κ(2) S:N] - Zhao, Jun (International Union of Crystallography, 2008)
The title compound, [Cu(2)(CN)(SCN)(C(10)H(8)N(2))(2)](n), contains two crystallographically independent Cu(I) atoms, each in a distorted tetrahedral geometry. Each Cu atom is coordinated by a bidentate chelating 2,2′-bipyridine ligand. A bridging cyanide anion links the two Cu(2,2′-bipyridine) units to form a binuclear unit. Adjacent binuclear units are connected by a thiocyanate anion into a one-dimensional helical chain along [010]. The cyanide anion is disordered, with each site occupied by both C and N atoms in an occupancy ratio of 0.61 (5):0.39 (5). The S atom of the thiocyanate anion is also disordered over two sites, with occupancy factors of 0.61 (3) and 0.39 (3). There are π–π interactions between the pyridyl rings of neighbouring chains [centroid–centroid distance = 3.82 (1) Å].